From Aesthetic Judgment to Political Judgment: On the Arendtian Reading of Kant - Ruiz Sanjuán, César (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
One of the most important and current dimensions of Hannah Arendt’s thought is her conception of judgment, which is also one of the most complex and controversial parts of her work. The fundamental problem facing any confrontation with the Arendtian theory of judgment is the absence of a complete exposition of it, which makes it necessary to reconstruct it on the basis of the preparatory materials published posthumously, in which Arendt translates into political terms the Kantian conception of aesthetic judgment. These materials must be contrasted in turn with the partial approaches to the faculty of judgment contained in various essays published by Arendt during her lifetime, in order to make a reconstruction of her theory as accurate as possible. This is what we propose to do in this paper, while avoiding to give an image of coherence where it does not exist and showing the questions that inevitably remain open on the basis of the available material.